Comparative analysis of COVID-19 vaccine responses and third booster dose-induced neutralizing antibodies against Delta and Omicron variants - Belik Milja; Jalkanen Pinja; Lundberg Rickard; Reinholm Arttu; Laine Larissa; Väisänen Elina; Skön Marika; Tähtinen Paula A.; Ivaska Lauri; Pakkanen Sari H.; Häkkinen Hanni K.; Ortamo Eeva; et al. (Nature Portfolio, 2025)
Vaccination shows efficacy in protecting from COVID-19, but regime and dosing optimization is still ongoing. Here the authors show that BNT162b2, mRNA-1273, or their combination with ChAdOx1 induces similar antibody responses, and those receiving three doses of BNT162b2 induce neutralizing antibodies against the Omicron variant.
Two COVID-19 mRNA (of BNT162b2, mRNA-1273) and two adenovirus vector vaccines (ChAdOx1 and Janssen) are licensed in Europe, but optimization of regime and dosing is still ongoing. Here we show in health care workers (n = 328) that two doses of BNT162b2, mRNA-1273, or a combination of ChAdOx1 adenovirus vector and mRNA vaccines administrated with a long 12-week dose interval induce equally high levels of anti-SARS-CoV-2 spike antibodies and neutralizing antibodies against D614 and Delta variant. By contrast, two doses of BNT162b2 with a short 3-week interval induce 2-3-fold lower titers of neutralizing antibodies than those from the 12-week interval, yet a third BNT162b2 or mRNA-1273 booster dose increases the antibody levels 4-fold compared to the levels after the second dose, as well as induces neutralizing antibody against Omicron BA.1 variant. Our data thus indicates that a third COVID-19 mRNA vaccine may induce cross-protective neutralizing antibodies against multiple variants.